Self-efficacy in Primary Schools Students as Potential Characters: From the Perspective of Students’ Self-ability and Interest - Rakhmawati, Yeni; Mustadi, Ali (Mimbar Sekolah Dasar, 2019)
Self-efficacy has an important role to strengthen one's belief in completing assignment. This research focused on lack of self-efficacy in primary school students. The purpose of this research is to describe the potentials and urgency of self-efficacy seen from the perspective of students’ self-abilities and interests in the fifth grade of primary schools. The subjects of this research were 108 students and 14 teachers in primary schools in Seyegan Sub-district, Sleman, Yogyakarta, which implemented the 2013 Curriculum. The object of this research was response self-efficacy. Moreover, a descriptive quantitative approach was adopted as the research method. The instruments of this research were a questionnaire and an open interview guidelines Data collection technique used a non-test method using questionnaire and an open interview guidelines. The findings revealed that: [1] students in the fifth grade of primary schools had started to show self-efficacy; [2] students were able to value themselves; [3] self-efficacy could develop into potential characters. Self-efficacy of students was able to be developed starting from primary schools.